PROYECTO DE INVERSIÓN PARA LA CREACIÓN DE UNA EMPRESA DE LAVADO Y SECADO DE ROPA EN LA CIUDAD DE ZUMBA, CANTÓN CHINCHIPE , PROVINCIA DE ZAMORA CHINCHIPE - Ordóñez Abad, Diana Paola (2016)
This project is in the feasibility analysis for the "CREATING AND DRYING CLOTHES IN THE CITY OF A COMPANY ZUMBA WASH Chinchipe Canton, province of Zamora Chinchipe." For the project initially the size of the sample, the purpose was to find the number of surveys to apply to the families of the city of Zumba 259 was determined, and thus develop the results where they proceeded to the collection of information surveys and then be tabulated, processed and interpreted; and thus present the results of the demand analysis is carried out in the Market Study, among them the unsatisfied demand was 104,389.30 kg, as well as the marketing plan and distribution channels to be used to provide the service. With the data obtained previously by the market research we proceed to the preparation of the Technical Study that represents the engineering of the project, installed and used here whose ability capacity amounts to 23,01% of the installed capacity is calculated 69.632,64 kg of clothing per year for all years of the project. In the optimal location of the project are located at the company as a micro location and macro location in the City of Zumba, streets May 24 and Calderon, against GAD Municipal Chinchipe, Streak is the legal and organizational study of the company concerning its economic activity "RAPILAVA" called Cia. Ltda .; and according to its hierarchy, your charts that graphically represent the new company and their respective function manuals that allow for better organization and unfolding of the activities to be performed by each member of the company are. 6 Then we have the financial study where investments in fixed assets, variables and their working capital, whose investment totaled $ 12,549.45 and will be financed by internal and external source, the internal source will be provided by the by partners $ 7549 are analyzed, 45 representing 60.16% and the remaining 39.84% is of $ 5,000.00 will be financed by the National Development Bank at a interest rate of 15.20% per annum, the costs will be projected for 5 years life with inflation at 3.67% obtained data of the Central Bank of Ecuador (2014), for determining the selling price we have a profit margin of 35% throughout the life of the project, giving a unit price in the first year of $ 0.90 and 1.05 for the fifth cents. The financial evaluation are the different financial indicators that allow assessing the profitability and feasibility of the project among these are the following: the net present value "VAN" amounting to $ 26,056.15 which ensures an increase in the value of the company at the end of the life of the project, the Internal Rate of Return (IRR) is 86.59% and this satisfactory value for it, the benefit cost determined that for every dollar we invested 0.39 cents , utility, the payback period of the investment will be in 1 year 1 month and 28 days, the sensitivity analysis on increased costs by 21.26% and a sensitivity of 0.9983 and the decline in revenues of 15.74 and a sensitivity of 0.99935, with positive values that do not affect the project's profitability. Finally it puts to consideration the conclusions where results have been obtained with this research as a contribution to its development are discussed.